ANALISIS ZONASI GERAKAN TANAH PADA DAERAH CIPINANG, KECAMATAN RUMPIN, KABUPATEN BOGOR: ZONING ANALYSIS OF LAND MOVEMENT IN THE CIPINANG AREA, RUMPIN DISTRICT, BOGOR DISTRICT - Afdhal, Muhammad; Yuda, Himmes Fitra (Universitas Trisakti, 2024)
The research was conducted in the Cipinang area, Rumpin District, Bogor Regency, West Java Province, which has regional conditions with varied morphology consisting of lowlands to highlands. From the existing geological conditions, the Cipinang area is an area with moderate to high susceptibility to landslides. One of the influencing factors is the slope from sloping to steep, and high rainfall. The aim of this research is to determine the ground movement vulnerability zone in the research area using a deterministic method in order to produce a map of the ground movement vulnerability zone using parameters that cause ground movement. with the final results obtained in the research area being divided into 3 zones, namely the low has coverage of 50%, the medium zone 40% and the high zone 10%.